Development and implementation of centralized simulation training: evaluation of feasibility, acceptability and construct validity. (29th August 2012) - Shamim Khan, Mohammad; Ahmed, Kamran; Gavazzi, Andrea; Gohil, Rishma; Thomas, Libby; Poulsen, Johan; Ahmed, Munir; Jaye, Peter; Dasgupta, Prokar
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? A competent urologist should not only have effective technical skills, but also other attributes that would make him/her a complete surgeon. These include team‐working, communication and decision‐making skills. Although evidence for effectiveness of simulation exists for individual simulators, there is a paucity of evidence for utility and effectiveness of these simulators in training programmes that aims to combine technical and non‐technical skills training. This article explains the process of development and validation of a centrally coordinated simulation program (Participants – South‐East Region Specialist Registrars) under the umbrella of the British Association for Urological Surgeons (BAUS) and the London Deanery. This program incorporated training of both technical (synthetic, animal and virtual reality models) and non‐technical skills (simulated operating theatres). Objectives To establish the feasibility and acceptability of a centralized, simulation‐based training‐programme. Simulation is increasingly establishing its role in urological training, with two areas that are relevant to urologists: (i) technical skills and (ii) non‐technical skills. Materials and Methods For this London Deanery supported pilot Simulation and Technology enhanced Learning Initiative (STeLI) project, we developed a structured multimodal simulation training programme. The programme incorporated: (i) technical skills training using virtual‐reality simulators (Uro‐mentor and Perc‐mentor [Symbionix, Cleveland, OH, USA], Procedicus MIST‐Nephrectomy [Mentice, Gothenburg, Sweden] and SEP Robotic simulator [Sim Surgery, Oslo, Norway]); bench‐top models (synthetic models for cystocopy, transurethral resection of the prostate, transurethral resection of bladder tumour, ureteroscopy); and a European (Aalborg, Denmark) wet‐lab training facility; as well as (ii) non‐technical skills/crisis resource management (CRM), using SimMan (Laerdal Medical Ltd, Orpington, UK) to teach team‐working, decision‐making and communication skills. The feasibility, acceptability and construct validity of these training modules were assessed using validated questionnaires, as well as global and procedure/task‐specific rating scales. Results In total 33, three specialist registrars of different grades and five urological nurses participated in the present study. Construct‐validity between junior and senior trainees was significant. Of the participants, 90% rated the training models as being realistic and easy to use. In total 95% of the participants recommended the use of simulation during surgical training, 95% approved the format of the teaching by the faculty and 90% rated the sessions as well organized. A significant number of trainees (60%) would like to have easy access to a simulation facility to allow more practice and enhancement of their skills. Conclusions A centralized simulation programme that provides training in both technical and non‐technical skills is feasible. It is expected to improve the performance of future surgeons in a simulated environment and thus improve patient safety.